PERATURAN PENANGANAN SAMPAH PLASTIK DI KOTA MAKASSAR DALAM MENGATASI PERUBAHAN IKLIM: REGULATIONS FOR HANDLING PLASTIC WASTE IN MAKASSAR CITY IN OVERCOMING CLIMATE CHANGE - Teguh Indraswara, Andi Iman; Hasan, Yulia A.; Oner, Basri (Faculty Of Law Bosowa University, 2021)
This study aims to find out all the obstacles experienced in overcoming climate change by handling single-use plastic waste in Makassar City, that makes Makassar City becomes the largest waste-producing area in Eastern Indonesia, and the legal rules used related to controlling the use of plastic do not can be implemented optimally. The research method used is descriptive qualitative. The research location is in Makassar City. Data collected by using literature review methods, interviews, observations, and documentation. The results showed that the obstacles to handling single-use plastic waste in Makassar City were local regulations that did not regulate the control of all types of single-use plastics, lack of public knowledge about the impact of single-use plastics, lack of long term assistance, inadequate and environmentally unfriendly waste processing facilities, and lack of awareness of perpetrators efforts to overcome the problem of single-use plastics.